Self as an Aesthetic Effect - Larrain, Antonia; Haye, Andrés (Frontiers in Psychology, 2019)
Mainstream psychology has assumed a notion of the self that seems to rest on a substantialist notion of the psyche that became predominant despite important critical theories about the self. Although cultural psychology has recognized the diverse, dialogical, historical, narrative and performative nature of self, as opposed to the idea of self as entity, it is not clear how it accounts for the phenomenological experience of self as a unified image. In this paper, we offer a theoretical contribution to developing the implications of a genetic approach to self in cultural psychology, taking into account an otherwise overlooked dimension: art and aesthetics. We draw on the work of classical authors relevant to cultural psychology, who, although geopolitically and theoretically diverse, are concerted in understanding human psychological life as part of a living process of becoming: James, Mead, Dewey, Vygotsky, Bakhtin and Vološinov. Overall, the hypothesis developed throughout the paper is that self is produced within psychological individuation as an effect of the aesthetic activity involved in everyday discursive life. We deepen the ideas that self is not an entity but a process of open becoming, and that cultural life entails a radical experience of alterity; but we recognize the psychological importance of the sense of unity and closure generated in this process. We argue that self entails not only the process of becoming, but also an aesthetical effect of unity in becoming. Self as an aesthetic effect emphasizes the self as a discursive and technical process of production, involving a product that, despite not being a finished entity, is felt as unitary and as mine by virtue of a specific transformation of experience. We thus propose to define self, on one level, as an epistemological category that points to the paradoxes of identity and agency in psychological individuation; and, on a different level, as a twofold operation that makes possible the subjective experience of a constitutive effort as much as a transient but experienced identity or agency.